ChatGPT-Assisted Interactive Speaking Practice: EFLStudents’ Perceptions - Ichda Aulia Rohmah; Irmayani; Anita Dwi Hapsari; Buyun Khulel; Syifa’ Khuriyatuz Zahro (Universitas Nusantara PGRI Kediri, 2026)
The use of generative Artificial Intelligence has increasingly influenced English Language Teaching, particularly in supporting speaking practice. One widely used AI tool is ChatGPT, which offers flexible opportunities for language learning. However, studies on students’ perceptions of its use in speaking activities at the senior high school level remain limited. This study aims to explore EFL students’ perceptions of using ChatGPT for speaking practice. This study employed a descriptive qualitative design. Data were collected through a questionnaire and supported by semi-structured interviews with selected students, and were analyzed using thematic analysis. The findings show that students perceive ChatGPT as a useful tool that provides additional opportunities for practice, increases confidence, and supports independent learning. However, several challenges were also identified, including over-reliance on the tool, uncertainty about the accuracy of responses, and the lack of real human interaction. Students also emphasized the importance of teacher guidance in using ChatGPT effectively and responsibly. These findings suggest that students’ perceptions should be considered in integrating AI tools into language learning, and that guided use of ChatGPT can support more meaningful speaking instruction.